One-Year Outcomes of Diabetes Self-Management Training Among Medicare Beneficiaries Newly Diagnosed With Diabetes. Issue 4 (April 2017) - Strawbridge, Larisa M.; Lloyd, Jennifer T.; Meadow, Ann; Riley, Gerald F.; Howell, Benjamin L.
Abstract : Background: Diabetes is highly prevalent among Medicare beneficiaries, resulting in costly health care utilization. Strategies to improve health outcomes, such as disease self-management, could help reduce the increasing burden of diabetes. Objectives: Short-term benefits of diabetes self-management training (DSMT) are established; however, longer-term impacts among Medicare beneficiaries are unknown. Research Design: Claims-based observational study with 1-year follow-up beginning 6 months after diabetes diagnosis. Subjects: Twenty percent random sample of Medicare beneficiaries newly diagnosed with diabetes during 2009–2011 who used DSMT (N=14, 680), matched to a nonuser comparison group. Measures: We compared health service utilization and costs between DSMT users and nonusers. Health service utilization included any utilization of the hospital or emergency department (ED) and any hospitalizations due to diabetes-related ambulatory care sensitive conditions as well as the number of hospitalizations and ED visits within the follow-up year. Costs included all Medicare Parts A and B expenditures. Results: Multivariate regression results found that DSMT users had 14% reduced odds of any hospitalization, lower numbers of hospitalizations and ED visits (approximately 3 fewer per 100 for each), and approximately $830 lower Medicare expenditures (95% CI, −$1198, −$470) compared with nonusers. Odds of any hospitalization due to diabetes-related ambulatory care sensitive conditions and any ED visit were lower for DSMT users compared with nonusers, but the reductions were not statistically significant. Conclusions: Findings demonstrate benefits from DSMT use, including lower health service utilization and costs. The low cost of DSMT relative to the reduction in Medicare expenditures highlights an opportunity to reduce the burden of diabetes on both individuals and the health care system.